Tectono-stratigraphy, formation and emplacement ages of the Beyşehir-Hoyran Nappes in the south of the Sultan Dağları (Isparta, SW Türkiye) - Aynur Hakyemez; Ayhan Ilgar; Ercan Tuncay; Alper Bozkurt; Ali Ergen (Bulletin of the Mineral Research and Exploration)
The Beyşehir-Hoyran Nappes (BHN), in the south of Sultan Dağları, consist of ophiolite, mélange and nappe slices of different lithologies and ages belonging to the oceanic crust and related rocks, which originated from the northern Neotethys and were thrusted southwards over the Taurus Platform. These nappes, namely the Marmaris ophiolite nappe, the Gülbahar nappe and the Domuzdağ nappe, are represented by three tectonically related nappe-slices that extend as a narrow NW-SE trending belt to the south of the Sultan Dağları. The Marmaris ophiolite nappe (Upper Cretaceous) is formed by three subunits namely the Marmaris ophiolite, the Kızılcadağ mélange and the Yenicekale metamorphics. Hornblende minerals from amphibolites of the Yenicekale metamorphic rock unit yielded a 40Ar-39Ar age of 93.9±0.34 Ma (Cenomanian-Turonian boundary). Besides, late Triassic to early Jurassic ages were obtained from the deep marine sedimentary rocks of the Gülbahar nappe based on the radiolarian assemblages.Paleontological and radiometric ages obtained from this study show that the formation of the BHN should began in the Turonian and ended in the Late Maastrichtian. The nappes, on the other hand, were emplaced over southern Sultan Dağları in the early-middle Paleocene and reached their present position as a result of late Eocene movements.